Letter (copy) : Scottish Trade Union foodship for Spain - Citrine, Walter, 1887-1983
030-0049-001 International. WMC/AEC/AT/395 Mr. W. Schevenels, International Federation of Trade Unions, 9 Avenue D'Orsay, Paris, 7. 20th September, 1938. Dear Comrade Schevenels, SCOTTISH TRADE UNION FOODSHIP FOR SPAIN We have duly received your wire giving us instructions for the marking of the above shipment to Valencia. We have now received from our Scottish friends particulars of the consignment and hasten to pass them on to you. 100 tons of Sugar at £7.12.6d. per ton. 70 " " Rangoon Beans at £10.0.0d. per ton. 50 " " Flour at £10.10.0d. per ton. 25 " (1000 cases) skimmed Condensed Milk at £16.0.0d. per ton. 45 " of Dried Fish at £15.0.0d. per ton. 20 " " Soap. Dried full cream milk to the value of about £550. In addition it is probable that 52 tons of food from Glasgow will be carried for delivery to the Scottish ambulance in Madrid. The ship will leave Glasgow at the latest 27th December. Yours sincerely, General Secretary. Acc. to invoices our shipment was 18 tons & the Glasgow TC to, total 28. see HVT letter & Glasgow TC letter for sources of figure of 45. 292/946/30/49